Congenital ring constrictions with entrapment neuropathies. - Marlow, N (1981)
An eight year old boy with multiple simple congenital ring constrictions is described with peripheral nerve palsies caused by entrapment in the constrictions. It is suggested that ring constrictions should be considered in the differential diagnosis of entrapment neuropathy.